2011
DOI: 10.1007/s00464-011-1814-y
|View full text |Cite
|
Sign up to set email alerts
|

Single incision laparoscopic (SILS) restorative proctocolectomy with ileal pouch-anal anastomosis

Abstract: SILS restorative proctocolectomy is safe with good early functional outcomes when performed by an experienced laparoscopic surgeon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 22 publications
1
32
0
Order By: Relevance
“…Several studies have reported SPLS feasi bility for ileocolonic resection for Crohn's disease 131,132 and IPAA for ulcerative colitis. [133][134][135] In a metaanalysis comparing SPLS to the standard laparoscopic approach for various conditions, we reported similar morbidity rates between the techniques and a reduced length of hospital stay after SPLS surgery. 136 However, these results were impaired by the retrospective design of the included studies.…”
Section: Factors Influencing Outcomessupporting
confidence: 58%
“…Several studies have reported SPLS feasi bility for ileocolonic resection for Crohn's disease 131,132 and IPAA for ulcerative colitis. [133][134][135] In a metaanalysis comparing SPLS to the standard laparoscopic approach for various conditions, we reported similar morbidity rates between the techniques and a reduced length of hospital stay after SPLS surgery. 136 However, these results were impaired by the retrospective design of the included studies.…”
Section: Factors Influencing Outcomessupporting
confidence: 58%
“…Since then, several series have been reported, for both adult and pediatric patient populations 7-9 , but only from single institutions and with short periods of follow-up 10 11 . Restorative proctocolectomy by single-incision laparoscopic surgery SILS is safe and associated with good early functional outcomes when performed by an experienced laparoscopic surgeon 12 . SILS is useful for optical assistance, colon dissection, and specimen retrieval [13][14][15] .…”
Section: Discussionmentioning
confidence: 99%
“…Although limited by a fairly low number of 5 patients with ulcerative colitis as well as familial adenomatous polyposis, they have shown technical feasibility of the method. In the following years SPLS proctocolectomy has also been investigated by other groups [42,43] . Gash et al [42] described a series of patients where restorative proctocolectomy was performed using a SPLS trocar through the existing or planed ileostomy site.…”
Section: Techniquementioning
confidence: 99%
“…In the following years SPLS proctocolectomy has also been investigated by other groups [42,43] . Gash et al [42] described a series of patients where restorative proctocolectomy was performed using a SPLS trocar through the existing or planed ileostomy site. In their analysis they reported no complications associated with the approach with good function of the pouch following ileostomy reversal.…”
Section: Techniquementioning
confidence: 99%